2021
DOI: 10.1007/s00184-021-00826-1
|View full text |Cite
|
Sign up to set email alerts
|

Some conditional reliability properties of k-out-of-n system composed of different types of components with discrete independent lifetimes

Abstract: In this paper, we study reliability properties of k-out-of-n system consisting of l$$(1\le l\le n)$$ ( 1 ≤ l ≤ n ) different types of components with discrete, independent lifetimes. We obtain some conditional survival functions of lifetime of a used system. Next, we use them to calculate two conditional failure probabilities of k-out-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Gao et al [5] suggested the ideal of an uncertain weighted k-out-of-n system and added an unknown variable to the weighted k-out-of-n system. A kout-of-n system with multiple sorts of components with discrete independent lifetimes was presented with certain conditional reliability qualities by Jasinski [9]. For a repairable consecutive k-out-of-n: F system, Gokhan et al [6], presented a time-dependent reliability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [5] suggested the ideal of an uncertain weighted k-out-of-n system and added an unknown variable to the weighted k-out-of-n system. A kout-of-n system with multiple sorts of components with discrete independent lifetimes was presented with certain conditional reliability qualities by Jasinski [9]. For a repairable consecutive k-out-of-n: F system, Gokhan et al [6], presented a time-dependent reliability analysis.…”
Section: Introductionmentioning
confidence: 99%